Legal Dynamics of Financial Responsibility and Marital Property in Indonesian Marriages - Rahmi Rahmi; Jayusman Jayusman; Nur Azizah; Efrinaldi Efrinaldi; Rahmawati Rahmawati (USRATY : Journal of Islamic Family Law, 2025)
This study explores the legal dynamics between financial responsibility and marital property in the context of marriages in Indonesia, with a specific focus on reconciling the normative gap between Islamic law and the Indonesia’s national legal system. While Islamic law places full financial responsibility (nafaqah) on the husband, Indonesian civil law applies a gender-neutral approach by recognizing joint marital property acquired during marriage, regardless of who earned it. This normative legal research employs a qualitative approach using statutory, conceptual, and comparative analyses of both Islamic legal texts (Qur’an, Hadith, and classical fiqh) and national legal instruments such as the Marriage Law No. 1 of 1974 and the Compilation of Islamic Law (KHI). The findings reveal a fundamental inconsistency: Islamic jurisprudence emphasizes the husband's economic duty, whereas civil law presumes equal ownership, potentially leading to legal ambiguity in divorce and inheritance cases. The study concludes that this dualism requires a contextual reinterpretation of the joint property regime that respects Islamic ethical values while adapting to modern socio-economic realities, including the increasing financial contributions of women. It is recommended that legal reforms recognize differentiated spousal roles without undermining gender justice. Proposing an integrative legal framework, this research bridges the gap between normative Islamic obligations and the state’s egalitarian legal principles. Such framework offers a more just, ethical, and socially relevant model for regulating financial responsibility and property rights in Muslim marriages within Indonesia’s plural legal system.